OPTIMIZATION OF Chlorella sp. FLOUR FORTIFICATION IN THE PROCESSING OF NATA - Juanidia Zulistiara; Syahrul '; Sumarto ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research aimed to study the effect of Chlorella sp.different weight and to find out the optimum weigth of Chlorella sp. flour fortified into the nata. The method used was experimental, that was fortification of Chlorella sp. flour in the processing of nata. The design used was a non-factorial completely randomized design, consisted of 4 weigth levels, namely: no Chlorella sp. flour added (N1), added with 2 gs Chlorella sp. Flour (N2), 4 gs Chlorella sp. flour (N3) and 6 gs Chlorella sp. flour (N4).The results were shown that the different weight of Chlorella sp. Flour added was affected to the characteristic of nata produced. The best nata was resulted from N4 treatment with addition of 6 gs Chlorella sp. Flour. It was characterized of no acid flavor (scored at 7,8), no acid aroma (scored at 7,4), contained 96,16% water, 1,36% protein and 1,29% crude fiber, the thickness at1,13 cm and the yield of 91%. Whilst, the highest score of the color and the texture was resulted from N2 treatment that was addition of 2 gs Chlorella sp. flour, indicated by the white color (scored at 7,1) and the chewy texture (scored at 7,5).Keywords: Chlorella sp flour, Fortification and Nata.